2020
DOI: 10.1111/php.13201
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal 3D Blood Flow Distribution Provided by Diffuse Correlation Tomography during Bone Healing in a Murine Fracture Model

Abstract: Noninvasive monitoring of vascularization can potentially diagnose impaired bone healing earlier than current radiographic methods. In this study, a noncontact diffuse correlation tomography (DCT) technique was employed to measure longitudinal blood flow changes during bone healing in a murine femoral fracture model. The three‐dimensional distribution of the relative blood flow was quantified from one day pre‐fracture to 48 days post‐fracture. For three mice, frequent DCT measurements were performed every othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…The SMM can be used in various longitudinal studies with different monitoring techniques and/or biological systems. For example, analysis of the longitudinal blood flow measured by diffuse correlation technique could evaluate the healing in bone injury [ 16 18 ] or the efficacy of chemotherapeutic drugs in breast cancer [ 25 ]. The monitoring techniques could be any spectroscopy or imaging techniques as long as they can provide longitudinal data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SMM can be used in various longitudinal studies with different monitoring techniques and/or biological systems. For example, analysis of the longitudinal blood flow measured by diffuse correlation technique could evaluate the healing in bone injury [ 16 18 ] or the efficacy of chemotherapeutic drugs in breast cancer [ 25 ]. The monitoring techniques could be any spectroscopy or imaging techniques as long as they can provide longitudinal data.…”
Section: Discussionmentioning
confidence: 99%
“…Different from allograft, autograft is harvested from the same injured mouse without devitalization. Therefore, autograft is regarded to have a better vascularization and healing potential [ 5 , 6 , 16 18 ]. However, the detailed temporal trend of the vascularization was not readily available, partially due to the lack of noninvasive monitoring tools.…”
Section: Introductionmentioning
confidence: 99%
“…Integrating recently developed time-of-flight methods (Sutin et al, 2016;Kholiqov et al, 2020) should be considered to improve CREPE for detecting deeper tissue signals without compromising spatial resolution. In addition, we hope the proposed fast parallelized speckle sensing method can be easily adapted to existing established, such as diffuse correlation tomography and speckle contrast optical tomography, to form three-dimension quantitative blood flow images in high speed (Zhou et al, 2006;Varma et al, 2014;Mazdeyasna et al, 2018;Ren et al, 2020). Moreover, as the proposed method relies on the entire set of autocorrelation curves rather than fitted values assuming relatively simple geometry of the heads, we expect the method can be used to separate different deep tissue dynamic events from both semi-infinite and non-semiinfinite geometries.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in bone fracture murine models, the blood flow in the fractured area decreased below the baseline level on the first day, peaked gradually, and further exhibited a general decrease with fluctuations. Additionally, group comparisons revealed that the earlier the blood flow peaked, the faster and more effectively the fracture healed ( Ren et al, 2020 ). In the bone graft healing model, the autograft group presented a peak in the blood flow in the first week, a decrease by half in the second week, and a steady decrease thereafter.…”
Section: Challenges and Prospectsmentioning
confidence: 99%